Miniaturization and broadbanding techniques for folded meander line microstrip antennas - Mohammad Ezanuddin, Abdul Aziz; Soh, Ping Jack; Liam, Ooi Soo; Majmi, M. M (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org